UTERUS DIDELPHYS IN NULLIPAROUS AND MULTIPAROUS WOMEN – A RARE ENTITY - SINHA, POOJA; JAGLAN, ANKITA; CHOUREY, NIRAJ; RAVISHEKAR N, HIREMATH; DAHIYA, DEEPTI; SANGWAN, ROOPA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Uterus didelphys is a rare congenital uterine abnormality in which the embryogenetic fusion of the Mullerian ducts fails to occur. It will lead to the formation of a double uterus with two separate cervices and most often a double vagina with a longitudinal septum as well. Here, we present two different cases of uterus didelphys with varied presentations. The first case is a nulliparous woman presented with post-coital bleeding. On examination, two cervical openings with a longitudinal complete vaginal septum were found, conservative management was done. Findings of didelphys uterus were confirmed on USG. The patient was counseled and discharged. The second case is a multiparous woman with previous cesarean delivery, rupture of membranes, and meconium in this pregnancy with term pregnancy taken up for emergency cesarean section. Dense adhesions and a mass on the right side of uterus were found intraoperatively, which on further inspection confirmed to be patent right horn of uterus. Diagnosis of uterus didelphys was made after doing per speculum and per vaginal examination post-cesarean.